Multimaterial 3D laser printing of cell-adhesive and cell-repellent hydrogels [data] - Schwegler, Niklas; Gebert, Tanisha; Villiou, Maria; Colombo, Federico; Schamberger, Barbara; Selhuber-Unkel, Christine; Thomas, Franziska; Blasco, Eva (Universität, 2024)
This study introduces a straightforward method for manufacturing 3D microstructured cell-adhesive and cell-repellent multimaterials using two-photon laser printing. Compared to existing strategies, this approach offers bottom-up molecular control, high customizability and rapid and precise 3D fabrication. The printable cell-adhesive PEG-based material includes an RGD-containing peptide synthesized through solid-phase peptide synthesis, allowing for precise control of the peptide design. Remarkably, minimal amounts of RGD peptide (< 0.1 wt%) suffice for imparting cell-adhesiveness, while maintaining identical mechanical properties in the 3D printed microstructures to those of the cell-repellent, PEG-based material. Fluorescent labeling of the RGD peptide facilitates visualization of its presence in cell-adhesive areas. To demonstrate the broad applicability of our system, we showcase the fabrication of cell-adhesive 2.5D and 3D structures, fostering the adhesion of fibroblast cells within these architectures. Thus, this approach allows for the printing of high-resolution, true 3D structures suitable for diverse applications, including cellular studies in complex environments.